Dietary risk factors for non-communicable diseases among Omani adults by latent class analysis and structural equation modelling - Al-Mawali, Adhra; Al-Harrasi, Ayaman; Pinto, Avinash Daniel; Morsi, Magdi; Balouchi, Abbas; Cappuccio, Francesco P. (BMC nutrition, 2025)
Background Risk factor surveillance is vital for public health interventions in non-communicable diseases (NCD) control due to a noticeable nutrition transition among the population affecting dietary patterns. The objective was to investigate the dietary risk factors and its associations based on a first-of-its-kind analysis employing both Latent Class Analysis (LCA) and Structural equation modelling (SEM) to explore the hidden heterogeneity and subgroups with shared dietary pattern and to demonstrate the complex interaction of dietary factors with other risk factors in the development of NCDs. Methods A cross-sectional survey was used. Secondary analysis of the 2017 Oman NCD Risk Factors Survey data was performed to investigate three major dietary risk factors (fruits and vegetables intake, eating out, and the type of oil used in cooking) of Omanis using LCA and SEM. Results Dietary risk factors are prevalent in Omanis with 55.8% reporting intake of less than five fruit and vegetable servings per day, 45.3% ate outside the home 1–3 times per week, and 87.3% used vegetable oil for cooking. LCA showed two distinct classes of Omani population with majority belonging to the class mainly eating out 1–3 times per week, eating less than the recommended servings of fruits and vegetables, vegetable oil users, educated, and married young adults. SEM showed the intricate interplay of dietary factors with 8 direct paths and several indirect paths with NCD indicators. Conclusions These findings may have important implications for targeting health promotion strategies among the high-risk group of Omanis identified in this analysis and inform decision makers for the reduction of NCDs.